Study on quantitative and qualitative features of somaclonal lines of wheat variety Kazakhstanskaya-10 (Experimental biology, 2015)
F2 generation plants of Kazakhstanskaya-10 variety, regenerated from tissue culture of immature embryos, served as material of the study.To detect changes on studied guantitative traits statistical parameters were used. Analysis of gliadin (wheat storageprotein) electrophoretic spectrum was carried out. It has been shown, that gliadin spectrum was identical for regenerantsand donor plants.
Keywords: regenerant; somaclone; quantitative features; qualitative features; gliadine; electrophoretic analysis